Macrozoobenthos as a Bioindicator for Kendedes River Water Quality in Malang, East Java - bagus, zidane; Kuntjhoro, Sunu (LenteraBio : Berkala Ilmiah Biologi, 2025)
The Kendedes River is a river that supports the activities of residents on its banks, such as bathing, washing, and some also use it for fishing. This river plays a crucial role in the lives of local communities, serving both as a source of agricultural irrigation and a provider of clean water. This research aims to identify the types of macrozoobenthos, analyse the macrozoobenthos diversity index, and determine water quality in terms of physico-chemical parameters, adjusted according to the quality standards of Government Regulation of the Republic of Indonesia No. 22 of 2021 concerning the implementation of environmental protection and management. This type of research combines both quantitative and qualitative observational methods. In this study, six species from five genera were identified, including Pilsbryoconcha exilis, Melanoides tuberculata, Melanoides maculata, Semyla riquetti, Pila ampullacea, and Sucospira testudinaria. This diversity index is then calculated using the Shannon-Wiener (H') formula. The Kendedes River in Malang, East Java, has a macrozoobenthos diversity index of 1.07, which falls within the medium diversity index category. The Kendedes River has an average BOD (Biological Oxygen Demand) of 1.24 and an average COD (Chemical Oxygen Demand) of 10.28, as measured according to the quality standards outlined in Government Regulation of the Republic of Indonesia No. 22 of 2021, which concerns the implementation of environmental protection and management. The Kendedes River, Malang, East Java, still meets quality standards when viewed in terms of the macrozoobenthos diversity index classification. The water quality in the Kendedes River, Malang, East Java, is classified as moderately polluted waters.